DNA Repair and Immune Response Pathways Are Deregulated in Melanocyte-Keratinocyte Co-cultures Derived From the Healthy Skin of Familial Melanoma Patients - Potrony, Miriam; Haddad, Tariq Sami; Tell-Martí, Gemma; Gimenez-Xavier, Pol; Leon, Carlos; Pevida, Marta; Mateu, Judit; Badenas, Celia; Carrera, Cristina; Malvehy, Josep; Aguilera, Paula; Llames, Sara; et al. (Frontiers in Medicine, 2021)
Familial melanoma accounts for 10% of cases, being CDKN2A the main high-risk gene. However, the mechanisms underlying melanomagenesis in these cases remain poorly understood. Our aim was to analyze the transcriptome of melanocyte-keratinocyte co-cultures derived from healthy skin from familial melanoma patients vs. controls, to unveil pathways involved in melanoma development in at-risk individuals. Accordingly, primary melanocyte-keratinocyte co-cultures were established from the healthy skin biopsies of 16 unrelated familial melanoma patients (8 CDKN2A mutant, 8 CDKN2A wild-type) and 7 healthy controls. Whole transcriptome was captured using the SurePrint G3 Human Microarray. Transcriptome analyses included: differential gene expression, functional enrichment, and protein-protein interaction (PPI) networks. We identified a gene profile associated with familial melanoma independently of CDKN2A germline status. Functional enrichment analysis of this profile showed a downregulation of pathways related to DNA repair and immune response in familial melanoma (P < 0.05). In addition, the PPI network analysis revealed a network that consisted of double-stranded DNA repair genes (including BRCA1, BRCA2, BRIP1, and FANCA), immune response genes, and regulation of chromosome segregation. The hub gene was BRCA1. In conclusion, the constitutive deregulation of BRCA1 pathway genes and the immune response in healthy skin could be a mechanism related to melanoma risk.